Manual de procesos de importación para la comercialización de urea, Empresa Agro Freire, años 2022. - Ruíz, Cristopher F. (2022)
In the area of ​​agriculture, different forms of cultivation of products and the application of inputs, which allow the passage for companies that are managed individually and segmented according to the activities they perform, the importation of agricultural products indicates the need for through the demand that is demanded by the farmers, with the purpose of optimize production, profit and quality in the production of raw material of Commodities, in this sense, the regulatory norms of a country should focus on the reduction of tariff barriers for tariffs with the objective to promote the import in this case for Ecuador.